The Effects of Tandem Stance Therapy on the Risk of Falling in the Elderly - Ni Made Dwi Yunica Astriani; Putu Indah Sintya Dewi; I Putu Indra Yudiastu; Made Mahaguna Putra (Poltekkes Kemenkes Surakarta, 2020)
Abstract: Tandem Stance Therapy is a therapy that is usually given to the elderly who are at risk of falling. The purpose of this study was to analyze the effect of tandem stance therapy on the risk of falling in the elderly in Giri Emas Village, Sawan District, Buleleng Regency. The research design was pre-experimental with one group pretest post-test design approach with a sample of 64 respondents selected using simple random sampling technique. Data collection was performed using the Morse Fall Scale (MFS) questionnaire. This study uses the Wilcoxon test. The results showed that the pre-test means value was 2.41 and the post-test score was 2.27. Wilcoxon test results obtained pretest and posttest (0.003) <α (0.05). It was concluded that there was an influence of Tandem Stance Therapy on Falling Risk in the Elderly in Giri Emas Village, Sawan District, Buleleng Regency.